4t-3=-13-2t

Simple and best practice solution for 4t-3=-13-2t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4t-3=-13-2t equation:


Simplifying
4t + -3 = -13 + -2t

Reorder the terms:
-3 + 4t = -13 + -2t

Solving
-3 + 4t = -13 + -2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '2t' to each side of the equation.
-3 + 4t + 2t = -13 + -2t + 2t

Combine like terms: 4t + 2t = 6t
-3 + 6t = -13 + -2t + 2t

Combine like terms: -2t + 2t = 0
-3 + 6t = -13 + 0
-3 + 6t = -13

Add '3' to each side of the equation.
-3 + 3 + 6t = -13 + 3

Combine like terms: -3 + 3 = 0
0 + 6t = -13 + 3
6t = -13 + 3

Combine like terms: -13 + 3 = -10
6t = -10

Divide each side by '6'.
t = -1.666666667

Simplifying
t = -1.666666667

See similar equations:

| 5.3+9.2x=7-4x-8.8 | | 1.8x+4.1x=5.7 | | 3.44-1.25=1.05(2.38x+6.81) | | 42x^2+10x=0 | | b=7x(-7) | | -3(2.47+1.25)=9.82 | | b=2x(-3) | | b=-2-4x(-3) | | E=-28+(5-2)*(-4) | | 3x+5=8-7x | | 35.13x-7.26=11-14.91x | | c=-22+(13-5)x(-5) | | y+11=15 | | -22+(13-5)x(-5)= | | 150+x+400=5000 | | 209-6x=30x+21 | | 2000=n(725-420) | | 8r+1=9 | | 4x+14=-19-7x | | 2x(3-x)=5x+7 | | x-2y=-26 | | -19x-21=80 | | 2x+9=7x-4 | | 7(t-2)-2=4 | | 900+x+65=1053 | | V=3.14*7*7*7 | | Y=x^2+2x-30 | | 900x+65=1053 | | 2(1-x)=2 | | 5=3y-1 | | 7x-16=x | | 6(x+2)=4x+30 |

Equations solver categories